Detection of Carbohydrate Antigen CA19-9 Levels in Sera and Tissues' Homogenate of Breast and Thyroid Benign Cases - Gheid H. Alubaidi; Zeyan A. Ali; Abdulrahman R. Mahmood (College of Pharmacy University of Baghdad, 2017)
The aims of the present study are to evaluate the levels of CA19-9 in sera and tissues' homogenate of breast and thyroid benign patients in order to assess its use as an early diagnostic parameter in differentiation between malignant and benign cases. The study was conducted on 8 patients with breast benign tumor and 8 patients with thyroid benign tumor, by the enzyme linked immunosorbent assay (ELISA) technique. The results of CA19-9 levels in sera were (15 Â±1.58 and 10.67 Â±2.08)U/ml respectively compared with serum CA19-9 levels of control group which was 7.74 Â±4.92 U/ml, the results were found to be highly significantly in breast tumor patients and non significantly in thyroid tumor patients than control group. The results of CA19-9 levels in tissues' homogenate were (356.2 Â±173.75 and 20 Â±14.4)U/ml respectively. The results were found to be highly significant in tissues' homogenate of breast tumor patients and non significant in thyroid tumor patients of higher compare with the it's serum levels of the same patients groups.   Key words: Carbohydrate antigen CA19-9, Benign Cases  and  CA19-9, Breast tumor  and CA19-9, Thyroid tumor  and  CA19-9.